2019
DOI: 10.1080/13603116.2019.1573938
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion and standards achievement: the presence of pupils identified as having special needs as a moderating effect on the national mathematics standards achievements of their classmates

Abstract: This article investigates the relationship between the achievement level of students in classes and the presence of students identified as having special needs in inclusive settings. In particular, it examines whether the presence of students with special educational needs in inclusive classrooms has an effect on the national mathematics standards achievement of their fellow students. In order to do so, the national standard scores of approximately 75,000 fourth graders in mathematics were used as dependent va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
2
8
2
Order By: Relevance
“…As this relationship tends to be negative, hypothesis (i.b) must be rejected. These results are comparable to the small effects revealed by Krammer et al (2019), who found both weak positive and weak negative effects for mathematics standard achievements depending on the exact number of students with SEN in a certain class. Additionally, these results do not contradict those of the recent meta-analysis from Szumski, Smogorzewska, and Karwowski (2017), who found a very weak (d = .12) positive effect on the academic achievement of students without SEN in inclusive settings.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…As this relationship tends to be negative, hypothesis (i.b) must be rejected. These results are comparable to the small effects revealed by Krammer et al (2019), who found both weak positive and weak negative effects for mathematics standard achievements depending on the exact number of students with SEN in a certain class. Additionally, these results do not contradict those of the recent meta-analysis from Szumski, Smogorzewska, and Karwowski (2017), who found a very weak (d = .12) positive effect on the academic achievement of students without SEN in inclusive settings.…”
Section: Discussionsupporting
confidence: 85%
“…Following Krammer et al (2019), the initial calculations were carried out with the Rpackage BIFIESurvey at a subsample of approximately 4500 students from 250 classes in 218 schools. The generated R-code was then sent to the BIFIE/IQS and applied to the complete data set.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations